Effects of warming and nitrogen fertilization on GHG flux in the permafrost region of an alpine meadow. (May 2017) - Chen, Xiaopeng; Wang, Genxu; Zhang, Tao; Mao, Tianxu; Wei, Da; Hu, Zhaoyong; Song, Chunlin
Abstract: The limited number of in situ measurements of greenhouse gas (GHG) flux during soil freeze-thaw cycles in permafrost regions limits our ability to accurately predict how the alpine ecosystem carbon sink or source function will vary under future warming and increased nitrogen (N) deposition. An alpine meadow in the permafrost region of the Qinghai-Tibet Plateau was selected, and a simulated warming with N fertilization experiment was carried out to investigate the key GHG fluxes (ecosystem respiration [Re], CH4 and N2 O) in the early (EG), mid (MG) and late (LG) growing seasons. The results showed that: (i) warming (4.5 °C) increased the average seasonal Re, CH4 uptake and N2 O emission by 73.5%, 65.9% and 431.6%, respectively. N fertilization (4 g N m −2 ) alone had no significant effect on GHG flux; the interaction of warming and N fertilization enhanced CH4 uptake by 10.3% and N2 O emissions by 27.2% than warming, while there was no significant effect on the Re; (ii) the average seasonal fluxes of Re, CH4 and N2 O were MG > LG > EG, and Re and CH4 uptake were most sensitive to the soil freezing process instead of soil thawing process; (iii) surface soil temperature was the main driving factor of the Re and CH4 fluxes, and the N2 O flux was mainly affected by daily rainfall; (iv) in the growing season, warming increased greenhouse warming potential (GWP) of the alpine meadow by 74.5%, the N fertilization decreased GWP of the warming plots by 13.9% but it was not statistically significant. These results indicate that (i) relative to future climate warming (or permafrost thawing), there could be a hysteresis of GHG flux in the alpine meadow of permafrost region; (ii) under the scenario of climate warming, increasing N deposition has limited impacts on the feedback of GHG flux of the alpine meadow. Highlights: Soil freeze-thaw cycles on GHG flux of the alpine meadow was investigated. Relative to climate warming, there could be a hysteresis of GHG flux in the alpine meadow of permafrost region. Increasing N deposition has limited impacts on GHG flux of the alpine meadow.